Effect of crude extracts of selected actinomycetes on biofilm formation of A. schindleri, M. aci, and B. cereus. (19th August 2014) - Saleem, Hafiz Ghulam Murtaza; Aftab, Usman; Sajid, Imran; Abbas, Zaigham; Sabri, Anjum Nasim
<x xml:space="preserve">Abstract</x> Actinomycetes are well known group of gram positive bacteria for their potential to produce antibiotics. This study sought to assess the ability of the selected actinomycetes to control biofilm forming bacteria isolated from different dental plaque samples. On the basis of morphological differences three out of ten different dental plaque bacterial isolates were selected for further study. These isolates were biochemically and genetically characterized and were identified as Acinetobacter schinndleri, Moraxella aci, and Bacillus cereus. Antibiotic resistant profile was measured through disc diffusion method and found that all three isolates were moderately sensitive to ofloxacin and erythromycin and resistant to trimethoprim. Antibacterial activity of ten different Streptomyces strains was assessed through an agar plug and well diffusion method against three dental biofilm forming bacteria. Two Streptomyces strains named as S. erythrogriseus and S. labedae showed good antibacterial activity against Moraxella and Acinetobacter strains. Ability of the four active antibiotic producing strains to inhibit biofilm formation was assessed using microtiter biofilm detection assay. It was found that biofilm forming ability of Acinetobacter and Moraxella was inhibited by S. labedae an antibiotic producing strain, while S. macrosporeus can only inhibit biofilm formation by B. cereus.